2012
DOI: 10.1371/journal.pone.0049961
|View full text |Cite
|
Sign up to set email alerts
|

The Ovicidal, Larvacidal and Adulticidal Properties of 5,5′-Dimethyl-2,2′-Bipyridyl against Drosophila melanogaster

Abstract: Insecticide resistance has limited the number of available chemical options for insect pest control. Hence there is a need for new chemistries with novel modes of action. Here we investigate the mode of action for an insecticide that has not yet been released for commercial use. The ovicidal, larvacidal and adulticidal effects of 5,5′-dimethyl -2, 2′-dipyridyl (termed Ha44), which is being developed as a treatment for head lice, were evaluated in the Drosophila melanogaster model system. Ha44 demonstrated sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Previous studies in D. melanogaster indicated that abametapir was capable of arresting a number of stages during embryogenesis. These inhibitory effects, however, were reversible following the addition of certain metal ions (Fe, Cu, and Zn; Van Hiel et al 2012 ). This finding is consistent with the proposed mechanism of action of abametapir, which, as a metal chelating agent, is capable of inhibiting metal-dependent processes, including metalloproteinases, in the louse egg.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies in D. melanogaster indicated that abametapir was capable of arresting a number of stages during embryogenesis. These inhibitory effects, however, were reversible following the addition of certain metal ions (Fe, Cu, and Zn; Van Hiel et al 2012 ). This finding is consistent with the proposed mechanism of action of abametapir, which, as a metal chelating agent, is capable of inhibiting metal-dependent processes, including metalloproteinases, in the louse egg.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the proposed mechanism of action of abametapir, which, as a metal chelating agent, is capable of inhibiting metal-dependent processes, including metalloproteinases, in the louse egg. Indeed, abametapir has previously been shown to inhibit a purified metalloproteinase Meprin A ( Van Hiel et al 2012 ), which has a similar protease domain structure to Zn metalloproteinase, Astacins, which are known to be involved in developmental morphogenesis in a number of species ( Sterchi et al 2008 ). Interestingly, the effects of the additions of Fe, Cu, and Zn to first-instar larvae differed from those additions made to eggs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Abametapir, or 5,5′-dimethyl-2,2′bipyridyl, is a heterocyclic organic molecule that inhibits metalloproteinases in part by chelating iron, copper, and zinc cations. 8,9 These metal cofactors are necessary for executing a range of functions in human lice, including the function of various metalloproteinases. 9,10 Metalloproteinases are critical for all stages of head lice ova development, egg hatching, and survival, and inhibition of these metalloproteinases is lethal.…”
Section: Drug Pharmacologymentioning
confidence: 99%